Gower Handbook of Project Management / Second Edition - Lock Dennis (Gower Publishing, 1996)
Project Management and its Organization, Contract Administration, Accounting and Finance, Planning and Scheduling, Managing Project Materials, Computers in Project Management, Managing Progress and Performance, Appendices.